Kajian Hukum Terhadap Peran Perusahaan Outsourcing Dalam Peningkatan Kesejahteraan Tenaga Kerja Di Indonesia - Jeni Pratista, Mawar; Zainuddin (Universitas Ekasakti, 2023)
Outsourcing practices have become an integral part of the labor market in Indonesia, with outsourcing companies playing a significant role in providing labor for various industrial sectors. This legal study aims to evaluate the role of outsourcing companies in enhancing the welfare of laborers in Indonesia. Through a juridical analysis approach, this study highlights the challenges and obstacles faced in the implementation of outsourcing practices, including legal uncertainties regarding employment relationships, the rights of outsourced workers, and adequate legal protection. The role of outsourcing companies in improving the welfare of laborers in Indonesia has significant implications for the protection of workers' rights, job security, and economic well-being. This study also emphasizes the decision of the Constitutional Court emphasizing the need for better legal protection for outsourced workers, followed by regulatory measures issued by the government. However, the implementation of these regulations still faces challenges in law enforcement and ensuring compliance by outsourcing companies.